Study of Ground Vibration Site Effects on Substation in Inhomogeneous Strata - Jingqiu Yang; Quanjun Zhu; Xinming Li; Jinrui Zhang; Xiaolin Li (Shock and Vibration)
A large substation confronts the risk of frequent tectonic earthquakes with a relatively high magnitude, thus it is necessary to analyze the seismic response of the site. To provide a reference for the seismic analysis of this substation, the seismic response of the substation site was investigated. Based on the Mohr–Coulomb elastic-plastic constitutive model, the finite element models of the soft soil site and engineering site were established, and the seismic responses of the soft soil site with and without backfill were analyzed. Subsequently, the effect of layered soil site on the acceleration amplification of various ground shocks was further studied, yielding the seismic acceleration amplification coefficients for soft soil site and engineering site. The results of the finite element model show that the seismic amplification factor of the soft soil site is 1.292. The seismic amplification factor of the engineering site varies under the action of simple harmonic wave, El Centro wave, and Kobe wave, with the amplification factors ranging from 1.092 to 1.405. Therefore, considering the effects of the spectral properties of seismic waves is essential for the seismic design.